Assessment of Oil Wastes Residual in Water, Sediment of Tigris River within Baghdad City - Zahraa ZahrawAl-Janabi (University of Thi-Qar Journal of Science, 2019)
This study conducted during  2013-2014 to investigated the effects of Oil Wastes and nutrients on the water /sediment quality of Tigris River in south of Baghdad, especially, the effluent that discharged from the Al-Doura oil refiner and the oil spills. Three station on the River were selected to be assessment point for the pollutions, the first one located at Al-Jaderria before Al-Doura oil refiner which represented the control area, the second station near Al-Doura oil refiner, while the third station located after Al-Doura oil refiner at Al-Zafrania , the result exhibit a series contamination of water/sediment samples by oil & grease and Total petroleum hydrocarbon, especially in station 2 where have the highest annual concentration levels of O/G and TPH, because its directly affected by the effluent discharge from the refiners. Moreover, the level of nutrient in sediment observed to be higher than that found in water sample.